Physiological Responses of Weaner Rabbits Fed Graded Levels of Poultry Litter - Owen, O.J.; Amakiri, A.O.; Ngodigha, E.M. (International Journal of Poultry Science, 2009)
A study was carried out to determine the effect of feeding graded levels of poultry litter on the physiological characteristics of rabbits. The litter was heat treated by deep stacking at a temperature range of 40.10-55°C (104.20-131°F) for 21 days. This was done to ensure pathogenic microbial safety when used as animal feed supplement. A twelve week feeding trial was conducted using 24 (2-3 months-old) Chinchilla rabbits to asses the effect of substituting Poultry Litter (PL) for Soya Bean Meal (SBM) on cortisol, total protein, cholesterol and enzyme serology of the rabbits. Soya bean meal in the diets was replaced with poultry litter at 0% (Diet A-Control), 5% (Diet B), 10% (Diet C) and 15% (Diet D). The rabbits were divided into four groups with each group assigned to one of the four dietary treatments in a Completely Randomized Block Design (CRBD). Each treatment was replicated three times. At the end of the feeding trial, blood samples were collected from three rabbits from each treatment group for cortisol, total protein, cholesterol and enzymological analysis. Results obtained showed that the inclusion of poultry litter had no significant (p>0.5) effect on cortisol, total protein, cholesterol and enzymes (Serum Glutamic Oxaloacetic Transaminase (SGOT), Serum Glutamic Pyruvic Transaminase (SGPT) and Alkaline Phosphatase (ALP). However, the rabbits on Diet A (0% PL) and Diet B (5% PL) gave better values numerically in cortisol and chemical components. This study justifies the practical possibility of having poultry litter as dietary protein source for animals using rabbits as a model and also provides an environmentally and economically friendly way of disposing this pollutant.